GE_GERICHTE P/6430/2021 vom 15. November 2021 - GE Cour de justice (2021)
IN DUBIO PRO REO;DISPOSITIONS PÉNALES DE LA LCR;RUPTURE DE BAN;EXEMPTION DE PEINE;FIXATION DE LA PEINE | LCR.95.al1.leta; CP.291; CP.47; CP.41.al1; CP.42.al1; CP.52